2021
DOI: 10.5539/ijb.v13n2p65
|View full text |Cite
|
Sign up to set email alerts
|

Rheophytic Adaptation of Eurya Japonica Thunb. (Ternstroemiaceae)

Abstract: Plants along rivers have narrow leaves to avoid the stress caused by the river’s flow during flooding. Plants that have undergone such morphological leaf modifications to adapt to rivers are called rheophytes. Some populations of Eurya japonica Thunb. (Ternstroemiaceae) were grown on riversides so that the comparative morphology and anatomy of leaves between riverside and inland (control) populations could be examined to confirm their rheophytic speciation. Our morphological and anatomical analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, future comparative studies of morphological and anatomical modifications of other organs, such as stem and root, between inland areas and serpentine areas will boost up our understanding of the adaptation of E. japonica into serpentine areas. Shiba et al (2021) indicated that six independent riverside populations of E. japonica experienced differentiation, including smaller leaves and higher stomata density. Moreover, populations of E. japonica are located in a small mosaic area of Kochi Prefecture in accordance with serpentine outcrops.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, future comparative studies of morphological and anatomical modifications of other organs, such as stem and root, between inland areas and serpentine areas will boost up our understanding of the adaptation of E. japonica into serpentine areas. Shiba et al (2021) indicated that six independent riverside populations of E. japonica experienced differentiation, including smaller leaves and higher stomata density. Moreover, populations of E. japonica are located in a small mosaic area of Kochi Prefecture in accordance with serpentine outcrops.…”
Section: Discussionmentioning
confidence: 99%
“…E. japonica was analyzed in a total of 60 individuals from the serpentine areas (30 from Ikou and 30 from Kagami) and 93 individuals from the inland areas (30 from Okina, 33 from Shigeto, and 30 from Noichi) (Figure 2). Shiba et al (2021) reported methods of morphological and anatomical analyses in E. japonica. Therefore, we followed these methods in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we performed morphological and anatomical analyses of L. japonicum based on Shiba et al (2021). For morphological analysis, the length, width, and thickness of the leaf blade were measured using a digital caliper and micrometer.…”
Section: Methodsmentioning
confidence: 99%